Two new species of Lepidocyrtus (Fractocyrtus) Cipola & Bellini (Collembola, Entomobryidae, Lepidocyrtinae), with new records and a new name for Lepidocyrtus (F.) americanus Cipola & Bellini, 2018 - Cipola, Nikolas Gioia; Viana, Stéphanie Dos Santos (Zootaxa, 2023)
Herein we propose a new name, Lepidocyrtus (Fractocyrtus) amazonaensis nom. nov. Cipola, to replace L. americanus Cipola & Bellini 2018, a combination preoccupied by Marlatt (1896). In addition to new geographic records for the species, two new species of Fractocyrtus are described: L. (Fractocyrtus) andensis sp. nov. from the Colombian Andes and L. (Fractocyrtus) chicomendesi sp. nov. from the Occidental Brazilian Amazon. The new species differs from other members of the subgenus in body color, dorsal chaetotaxy of the head, chaetotaxy of the third and fourth abdominal segment, postlabial chaetotaxy, trochanteral organ, collophore and furcula, beyond morphology on the lateral process of the labial papilla E. New patterns of body pseudopores are described and added to the new diagnosis for the subgenus. Fractocyrtus now has four species, with distribution from the Andes to the Oriental Brazilian Amazon.